Potensi dan Peran Kelembagaan Pertanian dalam Perlindungan Lahan Pertanian Pangan di Provinsi Bali - Putu Oka Suardi; Dwi Putra Darmawan; Gede Raka Sarjana (Universitas Udayana, 2016)
The achievement of self-sufficiency in rice in Bali province has a fairly severe constraints, because the conversion of wetland difficult to overcome. Therefore, control of land conversion through assign Sustainable Agricultural Land needs to be accompanied by efforts to strengthen agricultural institutions. This study was conducted to analyze: the potential of agricultural institutions in the protection of agricultural land sustainability, the role of agricultural institutions in the protection of agricultural land for food, agricultural potential in the provision of food for the population in the province of Bali, and in the second year of designing models of institutional strengthening agriculture safeguard sustainable food agricultural land in the province of Bali. To achieve these objectives, the research was conducted with survey design combined with the correlational approach (correlational research). Location research and respondents using purposive, while data analysis using the approach of Structural Equation Modeling (SEM) analysis using the soft ware SmartPLS M3 version 2.0., Followed by descriptive method. The results showed that: the potential of agricultural institutions in the protection of agricultural land is quite worth 66.72; the role of agricultural institutions in the protection of agricultural land classified as less instrumental with a value of 51.80; and projections of potential agricultural land in its main food supply rice seemed declining namely 90% (in 2015), 85% (in 2020) and 82% (in 2025).